A Management Framework of Islamic Micro Financing for Sustainable Palm Oil Farming - Ismail, Mohd. Adib; Ador, Sukainah Farhah; Mohd Shafiai, Muhammad Hakimi (Fakultas Ekonomi dan Bisnis, UNTAN, 2018)
The growth of demand and production in palm oil has increased rapidly from time to time, as this scenario has a positive impact on the development of economy. However, in the long run,the scenariomay give a negative impact if it is not closely controlled; like the issue of haze. Therefore, thisstudy is aimed to create a sustainable mechanism framework of palm oil farming among smallholders using Islamic micro financing.This is because; the position of smallholders is an issue in the sustainability debate in the palm oil industry at the global level. Using library research, this study discovered the constraints and the challenges faced by independent smallholders to create sustainable palm oil farming. Hence, the study was developed around the specific objectives that looked into the Islamic microfinance form and appropriate mechanisms for the implementation. In doing so, this study employed the qualitative method. From the results, it was concluded that Islamic microfinance is indeed a source of funding for a number of independent smallholders of oil palm. Later on, Islamic microfinance may contribute to sustainable palm oil production. Furthermore, by introducing a workable mechanism, more Islamic financial institutions should be involved in providing Islamic microfinancing to smallholders.